Star Formation in the Lopsided Galaxy Arp 291 - Irina S. Proshina; Dmitriy V. Oparin (The Astrophysical Journal)
We have investigated the star formation process taking place in the lopsided galaxy Arp 291, based on narrowband images in the H α , [N ii ] λ 6583, and [O iii ] λ 5007 emission lines, obtained using the modern tunable photometer MaNGaL at the Caucasus Mountain Observatory. We have diagnosed 30 star-forming (SF) regions by means of the Baldwin–Phillips–Terlevich method. The oxygen abundance of the ionized gas in the SF regions varies in the range from 8.17 ± 0.04 to 8.47 ± 0.16 dex, which is typical for spiral and irregular galaxies, and shows an anticorrelation with the surface density of current star formation rates. Star formation in the lopsided galaxy Arp 291 occurs in separate clumps comparable in size to those observed in spiral and lenticular galaxies, at a rate typical for these types of galaxies. The clumps of current star formation are located irregularly in the distorted spiral arms of Arp 291. Possible causes of lopsidedness of the galaxy are discussed.